The Effect of Memorization Model on Nursing Students’ Academic Achievement in Physiology Course a Study in Isfahan University of Medical Sciences - Athar Omid; Shaghayegh Haghjoo Javanmard; Fariba Haghani (مجله ایرانی آموزش در علوم پزشکی, 2014)
Introduction: Today's Medical education is associated with numerous complications including potential increase of data volume in clinical and theoretical learning environments. This requires for new strategies using appropriate instructional methods. This study was performed to investigate the effect of the memorization model on nursing students' academic achievement in physiology course. Methods: This quasi-experimental study with two groups of pre- and post-tests was conducted on all second semester nursing students, Students studying renal physiology were selected as the experimental group (n=48) and midwifery students studying physiology of kidney (n=46) and nursing students studying endocrine physiology course (n=48) were selected as control groups. All experimental sessions were held using Memorization model and control sessions were conducted through regular methods of lecture and slide show. Data was analyzed using descriptive statistics and inferential statistics, paired t-test, and ANOVA. Results: No statistically significant difference was found between mean scores of pretest which was 4.38±1.27 for experiment group and 4.15±1.79 for midwifery control group and 3.69±1.4 for nursing control group (p>0.05). There was a statistically significant difference between the mean scores of control group of nursing students (11.67±3.52) and experimental group (14.28±3.32), (p<0/001). Conclusion: Employing new teaching models such as memorization model that is appropriate with educational content can be effective in improving students’ learning. However, accomplishment in their application is affected by teachers’ ability to employ the model, students’ creativity skills, and study strategies.